1982
DOI: 10.1111/j.1475-097x.1982.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass of the axial and the appendicular skeleton in women with Colles' fracture: its relation to physical activity

Abstract: The aim of this investigation was to elucidate whether Colles' fractures in middle-aged women were indicative of generalized bone loss (osteopenia) and whether bone mass of the axial and the appendicular skeleton was related to the extent of daily physical activity. Thirty-six patients (aged 50-73 years) with previous Colles' fracture were studied. The median time elapse after the injury was 18 months (range 9-20.5 months). Bone mineral content of the 2nd, 3rd, and 4th lumbar vertebrae (lumbar BMC) and both di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Furthermore, Kr01ner et al ( 19) have found that the forearm bone mass of patients with Colles' fracture is~95% of age-matched women, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, Kr01ner et al ( 19) have found that the forearm bone mass of patients with Colles' fracture is~95% of age-matched women, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Krolner et al reported a higher lumbar BMD, measured by dual photon absorptiometry, in a group of middle-aged women with a high work capacity, compared with a group with a low work capacity (38). This group did not find any difference in forearm BMC between the two groups.…”
Section: Discussionmentioning
confidence: 84%
“…Most previous studies of bone loss from the distal radius in patients with Colles' fracture scanned at sites proximal to the fracture site (3,4,(6)(7)(8)(9), where the bone is mainly cortical; at those sites bone mineral content was 5-7% below normal. The one exception was the study by Hesp et al (5) in which UDR-BMD was measured by a combined computed tomography/ single photon absorptiometry technique.…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about the extent of bone loss from the ultradistal radius (UDR),I i.e., the distal 3 cm of the radius, in women with type I osteoporosis and Colles' fracture or the relationship of loss at this site to loss in the vertebrae. Most densitometric measurements have been made proximal to the usual site of Colles' fracture, in a region containing 5-50% trabecular bone (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%